Performative Significance of Malashree Songs of Salyan District of Nepal - Raj Kumar, Tharu; Sharma, Bal Krishna (Academia Research Journal, 2026)
The Malashree is a common traditional Nepali folk song. It is also sung in different mountainous areas such as Salyan district in Nepal. In this qualitative study, we have utilised the performance theory of Richard Schechner in the special consideration of the performative facet of the Malashree song and the cultural, social, devotional and transformative meaning of the song. As our research shows, Malashree goes beyond the conventional definition of ritual music to influence several other activities of the community. We have absorbed the primary and the secondary data sources that we have in order to examine its historical roots and analyse its musical components by showing how the Malashree songs capture the religious and cultural identity especially at the Dashain festival. Songs practised by the Malashree in Salyan especially, do not serve purely religious functions but they also serve as an indicator of social unity, social cohesion and group attachment. This scholarly paper is set to critically examine and explore its religious value particularly in religious rites. The paper moreover, highlights their role in glorifying the goddess Durga or Bhagwati during the festive occasion. The study stresses on need of the preservation the musical performative heritage of Malashree songs for the reason that its existence at present is at risk due to changing socio-cultural dynamics. So, to keep this heritage alive and to pass it from one generation to the next, it is very important to keep its cultural relevance. The study comes up with the idea that the performative culture itself leads to a better understanding of Malashree as a living cultural legacy, which can be an important part of shaping community identity, social structure, and a shared sense of tradition and devotion. Malshree song practicing communities in Salyan district of Nepal have made a significant contribution to the preservation of the musical tradition alive.